Reengineering for revenue growth - Angus, F. Raymond (Research management (Now: research technology management))
F. Raymond Angus, Alan L. Goodman, Phil Pfund, Robert Wasson, Ralph Wyndrum and Walter M. Zoller examine the role of R&D in achieving corporate reengineering goals.